A solidariedade social e política na perspectiva freireana: um estudo sobre o Comitê Amor pela Vida (COMAV) na Escola Fenelon Câmara - Barreto , Kadydja Menezes da Rocha (2020)
The present research aims to identify, characterize and analyze the presence of the Social and Political Solidarity from a Freire inspiration in the activities of the Comitê Amor pela Vida (Love for Life Committee) (COMAV), located at the Municipal Elementary School Fenelon Câmara, which Is located at Geisel neighborhood in city of João Pessoa / Paraíba / Brazil. We payed attention to the experiences of the boys and the girls who participate in COMAV, as an emancipatory experience in the context of Human Rights Education. The theoretical proposal that guides the study is based on Paulo Freire pedagogy in his dialogue with the Popular Education, Education in Human Rights and with the Critical Social Pedagogy. The path of this scientific investigation was built from the assumptions of the participant research, having as main focus the reflection around the actions developed by COMAV inside and outside the school space. The instruments adopted for data collection were: participant observation, document analysis and interview. During the course of the research, because of the mandatory social isolation as a preventive measure to COVID - 19, the questionnaire technique was adopted. Therefore, was presented: the historical-social context of public policies with children and adolescents, the construction of the conceptions of social and political solidarity in the professor Paulo Freire's pedagogical thought sandals of the identification and characteristics of COMAV's actions. Theseactionswerethoughtsaccordingtothetheoreticalmethodologicalprinciplesof popular education, human rights education and critical social pedagogy. Thusly, we present the possibilities of feel, think and act of the social and political solidarities inspired by Freire as a presence that’s happens the creativity, curiosity, and criticality of the adolescents' leading role in the public schools pace. At the end of this wanderings, it was possible to understand that the Love for Life Committee emerges through five dimensions: youth protagonism, the social action of the school, the community dimension, education for the senses and education in human rights. Thinking about these dimensions, we could conclude that there are strong indications of the social and political solidarity of Freire's inspiration in the actions developed by COMAV, because of the pedagogical practices constituted with and for the other through the dialogue as an exercise of thinking about the human existence from the social commitment and mutual trust between subjects as a methodology of struggle in favor of the least favored.